The Role of Government Spending, FDI, and Infrastructure Energy on Poverty between Regions in Riau Province; Spatial Approach - Murialti, Neng; Hadi, M. Fikry; Hidayat, Muhammad; Minovia, Arie Frinola; Ramadona, Midespa (International Journal of Energy Economics and Policy, 2025)
This study attempts to investigate poverty that occurs between regions in Riau Province in the form of trends that occur and the role of government spending, FDI, and energy infrastructure on poverty levels, as well as spatial dependence from neighboring areas. This study uses panel data from 12 districts/municipalities for the period 2011–2023 with a spatial econometric approach - spatial durbin model (SDM). The results found that the overall poverty trend has decreased, with the highest figure in Meranti district and the municipal area at 3%. The results of the spatial regression found that government spending, last year’s FDI, and economic growth significantly increased poverty. In addition, the results of this study provide evidence that the influence of neighboring regional characteristics significantly affects the decline in poverty levels in key areas such as government spending on social aid, economic growth, education, and infrastructure energy.